Pengaruh Dosis Pupuk N terhadap Pertumbuhan dan Hasil Sorgum Varietas Watar Hammu Miting Nggangga - Pameling, Marselinus Teduh; Suprihati, Suprihati (Sekolah Tinggi Pertanian Kutai Timur, 2025)
Sorghum (Sorghum bicolor L.) is one type of cereal plant that is widely planted in areas with hot and dry climates so that it has good adaptation. One type of local sorghum variety is Watar Hammu Miting Nggangga which comes from East Sumba, NTT which is adapted in Kopeng, Central Java. This study used an experimental method (RAK) and 5 N dose treatments (control; 2.44 g/plant; 3.69 g/plant; 4.89 g/plant; 6.08 g/plant) arranged in 4 groups. The parameters observed were plant height, number of leaves, stem diameter, dry stalk weight, panicle length, seed weight, 100 seed weight. The N dose of 3.69 g/plant gave the highest average results for plant height with an average value of 121.6 cm, seed weight per plant with an average value of 57.27 g, panicle weight with an average value of 543.16 g, leaf chlorophyll with an average value of 57.27 mg/cm2. With these results, the N fertilizer dose did not provide a significant difference for the Watar Hammu Miting Nggangga sorghum variety.